2021
DOI: 10.1016/j.antiviral.2021.105057
|View full text |Cite
|
Sign up to set email alerts
|

Effective deploying of a novel DHODH inhibitor against herpes simplex type 1 and type 2 replication

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…While the combination of DPY with inhibitors of de novo pyrimidine biosynthesis has been investigated previously to increase the anticancer effects of the latter compounds [ 46 ], the potential of this combination against virus infections has not yet been thoroughly explored. To this regard, we have recently observed the efficacy of a synergistic combination of MEDS433 with DPY in suppressing the in vitro replication of Herpes simplex virus type 1, even in the presence of hyperphysiological concentration of uridine [ 47 ]. Importantly, the DPY concentrations observed to be effective in combination with MEDS433 were lower than the DPY C max [ 48 ], and therefore clinically achievable in patients treated with DPY.…”
Section: Discussionmentioning
confidence: 99%
“…While the combination of DPY with inhibitors of de novo pyrimidine biosynthesis has been investigated previously to increase the anticancer effects of the latter compounds [ 46 ], the potential of this combination against virus infections has not yet been thoroughly explored. To this regard, we have recently observed the efficacy of a synergistic combination of MEDS433 with DPY in suppressing the in vitro replication of Herpes simplex virus type 1, even in the presence of hyperphysiological concentration of uridine [ 47 ]. Importantly, the DPY concentrations observed to be effective in combination with MEDS433 were lower than the DPY C max [ 48 ], and therefore clinically achievable in patients treated with DPY.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine cell viability, the confluent VERO cells were exposed to increasing concentrations of the peptides (12.5, 25.0, or 50.0 μg mL −1 ), the plate was incubated for 72 h at 37 °C. The number of viable cells was determined using the CellTiter-Glo Luminescent assay (Promega), as described in Luganini et al [ 51 ]. The peptides were assessed for their antiviral activity at a concentration that produced at least 70% cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…Calistri et al demonstrated that MEDS433 inhibited in vitro replication of HCoV-OC43 (EC 50 = 0.012 μM), HCoV-229E (EC 50 = 0.022 μM), and SARS-CoV-2 (EC 50 = 0.063 μM in Vero E6, EC 50 = 0.076 μM in Calu-3) at nanomolar range with low toxicity [ 90 ]. Luganinia et al demonstrated that MEDS433 inhibited herpes simplex virus-1 and -2 in vitro (EC 50 ~0.1 μM) and exhibited highly synergistic antiviral activity when combined with acyclovir (a DAA) in a checkerboard assay [ 91 ].…”
Section: Dhodhi Applications In Antiviral Treatmentmentioning
confidence: 99%